Case report: An exceptional responder of low-dose continuous 5-FU in a patient with de-novo stage IV triple-negative breast cancer with liver and bone marrow failure - Chan, Bryan; Lee, Jin Sun; Yuan, Yuan (Frontiers in Oncology, 2024)
Continuous low dose 5-FU was popularized as a therapy for pretreated metastatic breast cancer for the past few decades, spurred by the advent of the electronic infusion pump. Capecitabine, otherwise known by its trade name Xeloda, is a prodrug of 5-fluorouracil (5-FU), which is administered orally in many chemotherapy regimens, and plays a role in metastatic breast cancer treatment refractory to traditional anthracyclines and taxane therapy. In this case presentation, we describe a unique case of refractory de novo stage IV triple negative breast cancer presented with right breast primary invasive ductal carcinoma, extensive lymphadenopathy, with biopsy proven bone marrow infiltration, diffuse hepatomegaly, splenomegaly, significant hyperbilirubinemia and bone marrow failure treated with continuous 5-FU infusion and subsequently oral capecitabine after initial treatment failure with nab-paclitaxel, and sacituzimab govitecan. With this case presentation, the authors aim to showcase the versatility of 5-FU and its prodrug in treatment of metastatic triple negative breast cancer with severe bone marrow and liver involvement, while highlighting key physiologic and pharmacologic mechanisms.